2021
DOI: 10.3389/fendo.2021.680609
|View full text |Cite
|
Sign up to set email alerts
|

Carney Triad, Carney-Stratakis Syndrome, 3PAS and Other Tumors Due to SDH Deficiency

Abstract: Succinate dehydrogenase (SDH) is a key respiratory enzyme that links Krebs cycle and electron transport chain and is comprised of four subunits SDHA, SDHB, SDHC and SDHD. All SDH-deficient tumors are caused by or secondary to loss of SDH activity. As many as half of the familial cases of paragangliomas (PGLs) and pheochromocytomas (PHEOs) are due to mutations of the SDHx subunits. Gastrointestinal stromal tumors (GISTs) associated with SDH deficiency are negative for KIT/PDGFRA mutations and present with disti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 129 publications
(186 reference statements)
0
9
0
1
Order By: Relevance
“…In histological examination, these tumors are characterized by a multinodular growth pattern with epithelioid cells, which are multifocal. Additionally, it was found that SDH-deficient GISTs overexpress insulin-like growth factor receptors (IGF1R) [ 18 ]. Testing for germline mutations in SDH should be considered in young adults with GISTs wild type for KIT/PDGFRA mutations.…”
Section: Biology and Molecular Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…In histological examination, these tumors are characterized by a multinodular growth pattern with epithelioid cells, which are multifocal. Additionally, it was found that SDH-deficient GISTs overexpress insulin-like growth factor receptors (IGF1R) [ 18 ]. Testing for germline mutations in SDH should be considered in young adults with GISTs wild type for KIT/PDGFRA mutations.…”
Section: Biology and Molecular Biologymentioning
confidence: 99%
“…Carney’s triad is usually caused by a specific pattern of methylation of the SDHC gene and may be due to germline mosaicism of the responsible genetic defect. Carney-Stratakis syndrome is instead caused by inactivating germline mutations in genes encoding for the SDH subunits [ 18 ].…”
Section: Biology and Molecular Biologymentioning
confidence: 99%
“…The summary of the main characteristics of SDH-deficient GIST is presented in table I and II. Over 80% of pediatric GIST has inactivating mutations in SDH subunits [23,24].…”
Section: Clinical and Molecular Features Of Sdh-deficient Gistsmentioning
confidence: 99%
“…Succinate dehydrogenase (SDH, also known as mitochondrial complex II or succinate-ubiquinone oxydoreductase) is a highly conserved heterotetrameric enzyme complex (composed of four protein subunits -SDHA, SDHB, SDHC, and SDHD, encoded by nuclear genes, mapped to 5p15.22, 1p36.13, 1q23.3 and 11q23.1, respectively), which acts at the interphase of the tricarboxylic acid cycle and electron transport chain. SDH is the only enzyme that is concurrently both a functional member of both the Krebs cycle and the electron transport chain (ETC), where it provides electrons for oxidative phosphorylation [24].…”
Section: Clinical and Molecular Features Of Sdh-deficient Gistsmentioning
confidence: 99%
“…Примерно у 50% пациентов с дефицитом SDH имеет место гиперметилирование промотора SDHC, у 30% -мутации генов SDHA и у 20% -мутации SDHB, SDHC, SDHD. Мутации и эпигенетические изменения приводят к потере экспрессии одной из субъединиц комплекса и к накоплению в клетке сукцината, который ингибирует семейство 5-метилцитозингидроксилаз TET, которые превращают 5-метидцитозин в 5-гидроксиметилцитозин (деметилируют цитозин), что в дальнейшем приводят к изменению метилирования ДНК [8]. Инактивация SDH вызывает активацию сигнальных путей, что приводит к усилению ангиогенеза и клеточной пролиферации [9].…”
Section: Introductionunclassified